Acts of Enjoyment : Rhetoric, Zizek, and the Return of the Subject - Rickert, Thomas J. (Thomas Joseph), 1964- (Book collections on Project MUSE., 2007)
Why are today's students not realizing their potential as critical thinkers? Although educators have, for two decades, incorporated contemporary cultural studies into the teaching of composition and rhetoric, many students lack the powers of self-expression that are crucial for effecting social change.Acts of Enjoymentpresents a critique of current pedagogies and introduces a psychoanalytical approach in teaching composition and rhetoric. Thomas Rickert builds upon the advances of cultural studies and its focus on societal trends and broadens this view by placing attention on the conscious and subconscious thought of the individual. By introducing the cultural theory work of Slavoj Zizek, Rickert seeks to encourage personal and social invention--rather than simply following a course of unity, equity, or consensus that is so prevalent in current writing instruction. He argues that writing should not be treated as a simple skill, as a naïve self expression, or as a tool for personal advancement, but rather as a reflection of social and psychical forces, such as jouissance (enjoyment/sensual pleasure), desire, and fantasy-creating a more sophisticated, panoptic form. The goal of the psychoanalytical approach is to highlight the best pedagogical aspects of cultural studies to allow for well-rounded individual expression, ultimately providing the tools necessary to address larger issues of politics, popular culture, ideology, and social transformation.